Detection of Helicobacter pylori with clarithromycin resistance‐associated mutations using peptide nucleic acid probe‐based melting point analysis. Issue 5 (14th July 2019) - Nahm, Ji Hae; Kim, Won Kyu; Kwon, Yujin; Kim, Hyunki
Abstract: Background: Detection of Helicobacter pylori in gastric biopsy is important for appropriate treatment and prevention of gastric carcinoma and lymphoma. A novel peptide nucleic acid probe (PNA)‐based real‐time polymerase chain reaction (PCR) method was developed for detection of H pylori and A2142G/A2143G mutation of the 23S rRNA gene, which is associated with clarithromycin resistance. Methods: To evaluate the performance of the PNA probe‐based PCR method, a total of 409 gastric biopsy samples were analyzed by PNA probe‐based PCR and compared with other H pylori detection methods, including hematoxylin and eosin (HE) and Warthin‐Starry (WS) staining, immunohistochemistry (IHC). A2142G/A2143G mutation of the 23S rRNA gene was tested by dual priming oligonucleotide (DPO)‐based PCR and Sanger sequencing to evaluate PNA probe‐based PCR. Results: Among 271 cases that were positive for H pylori on IHC which was considered as a standard method, 264 cases (97.4%) and 259 cases (95.6%) were positively detected by HE/WS and PNA probe‐based qPCR, respectively. Of 100 H pylori‐ positive patients tested by IHC, H pylori was detected in 93 cases (93.0%) by PNA probe‐based PCR, 86 cases (86.0%) by DPO‐based PCR, and 93 cases (93.0%) by conventional PCR. The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of PNA probe‐based qPCR were 93.0%, 94.9%, 93.9%, 94.9%, and 93.0%, respectively, which were all higher than those of DPO‐based PCR. When Sanger sequencing was determined as a standard method to detect A2142G/A2143G mutations, the sensitivity of the PNA‐ and DPO‐based methods was 100% and 94.4%, respectively, and the specificity was 100% for both methods. Conclusion: PNA probe‐based qPCR is an appropriate method for detecting H pylori and the clarithromycin resistance‐associated mutation type.